Gender-Responsive School Development in the Implementation of Kurikulum Merdeka (Independent Curriculum): A Case Study of SMA Negeri 7 Purworejo - Husna, Nur Sallama; Mintarti; Tri Wuryaningsih (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
This study aims to analyze the efforts of school in developing gender-responsive schools, the indicators of gender-responsive schools, and the challenges encountered in implementing the Independent Curriculum. The background of this study lies in the urgency of gender-responsive education to fulfill the needs of each gender fairly and equally in the field of education. The study employed a descriptive qualitative research method. The informants included school principals; vice principals for curriculum, facilities and infrastructure, student affairs, and public relations; teachers; and students, who were selected using purposive sampling. Data were collected through interviews, observation, and documentation. The validity of the data was ensured through triangulation of sources, techniques, and time. Data analysis was carried out using the interactive model proposed by Miles, Huberman, and Saldana. The findings show that several efforts made by school to build gender-responsive schools within the framework of the Independent Curriculum. These include implementing differentiated learning, strengthening the capacity of teachers and staff, developing gender-sensitive P5 programs, integrating gender perspectives into teaching modules, and establishing TPPKS. Indicators of gender-responsive schools in the context of the Independent Curriculum can be observed through the standards of graduation, content, teaching and learning processes, teachers and educational staff, facilities and infrastructure, school management, financing, assessment, students, and community participation. The challenges in implementing the Independent Curriculum include limited time, diverse assessment formats, and the lack of offline training programs.